Volatile and light lithophile elements in high-anorthite plagioclase-hosted melt inclusions from Iceland. (15th May 2017) - Neave, David A.; Hartley, Margaret E.; Maclennan, John; Edmonds, Marie; Thordarson, Thorvaldur
Abstract: Melt inclusions formed during the early stages of magmatic evolution trap primitive melt compositions and enable the volatile contents of primary melts and the mantle to be estimated. However, the syn- and post-entrapment behaviour of volatiles in primitive high-anorthite plagioclase-hosted melt inclusions from oceanic basalts remains poorly constrained. To address this deficit, we present volatile and light lithophile element analyses from a well-characterised suite of nine matrix glasses and 102 melt inclusions from the 10 ka Grímsvötn tephra series (i.e., Saksunarvatn ash) of Iceland's Eastern Volcanic Zone (EVZ). High matrix glass H2 O and S contents indicate that eruption-related exsolution was arrested by quenching in a phreatomagmatic setting; Li, B, F and Cl did not exsolve during eruption. The almost uniformly low CO2 content of plagioclase-hosted melt inclusions cannot be explained by either shallow entrapment or the sequestration of CO2 into shrinkage bubbles, suggesting that inclusion CO2 contents were controlled by decrepitation instead. High H2 O/Ce values in primitive plagioclase-hosted inclusions (182–823) generally exceed values expected for EVZ primary melts ( ∼ 180), and can be accounted for by diffusive H2 O gain following the entrainment of primitive macrocrysts into evolved and H2 O-rich melts a few days before eruption. A strong positive correlation between H2 O and Li in plagioclase-hosted inclusions suggests that diffusive Li gain may also have occurred. Extreme F enrichments in primitive plagioclase-hosted inclusions (F/Nd = 51–216 versus ∼15 in matrix glasses) possibly reflect the entrapment of inclusions from high-Al/(Al + Si) melt pools formed by dissolution-crystallisation processes (as indicated by HFSE depletions in some inclusions), and into which F was concentrated by uphill diffusion since F is highly soluble in Al-rich melts. The high S/Dy of primitive inclusions (∼300) indicates that primary melts were S-rich in comparison with most oceanic basalts. Cl and B are unfractionated from similarly compatible trace elements, and preserve records of primary melt heterogeneity. Although primitive plagioclase-hosted melt inclusions from the 10 ka Grímsvötn tephra series record few primary signals in their volatile contents, they nevertheless record information about crustal magma processing that is not captured in olivine-hosted melt inclusions suites.